MEDICAL IMAGE ENCRYPTION USING DNA ENCODING AND MODIFIED CIRCULAR SHIFT - Santoso, Kiswara Agung; Kamsyakawuni, Ahmad; Seggaf, Muhammad (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
This paper proposes a new encryption method for the encryption of medical images. The method is used to divide the image into several blocks and then scramble the image blocks using DNA chains and then shift the pixels in a circle with certain rules. To provide a more secure result, the input key contains a DNA chain and is equipped with complementary rules, and is converted into a hexadecimal number using a DNA coding table. Experimental results and values of NPCR and UACI show that the scheme achieves good encryption and decryption results.